Exit or Voice? The Recent Drivers of Kosovar Out‐migration. (2nd May 2017) - Möllers, Judith; Arapi‐Gjini, Arjola; Herzfeld, Thomas; Xhema, Sherif
Abstract: A remarkable out‐migration from Kosovo occurred after the winter 2014/15, raising urgent questions about its underlying drivers and implications for both Kosovo and the destination countries. This article aims at providing a better understanding of key migration triggers and some particularities of the phenomenon. We link our empirically found migration drivers to Hirschman's (1970 ) famous exit, voice or loyalty scheme by asking in how far the exit must be understood as the explicit alternative to voicing dissatisfaction with the current situation in the country. According to our results, the recent Kosovar out‐migration is a clear response to weak governance and thus goes beyond the widespread 'migration‐cum‐remittances' livelihood practice. In this sense it could be interpreted as a revolt against the political system. With view to policy implications for destination countries, we point at legal travel and migration opportunities as the better solution to channel both voice and exit.